Faktor-Faktor Penyebab Pengulangan Citra pada Modalitas Digital Radiography: Sebuah Studi Observasional - Muhammad Rusli; Nurul Aulyaa Hasbi; Nurul Jannah Jamal (Lontara Journal of Health Science and Technology, 2026)
Digital radiography produces digital images whose quality determines the accuracy of the diagnosis. The method to ensure quality is image repeat analysis. The study aims to analyze the percentage of repeat images of Digital Radiography (DR) modality in the Radiology Installation of Bhayangkara Hospital Makassar in March - April 2025. The method used in this study is quantitative with an observational approach. Data were collected through direct observation and recording of daily examinations as well as data from the DR consult computer for the period March to April 2025. The results of the study stated that the average percentage of repeat radiographic images in March-April 2025 was 3.41% in March 2.18% and in April 2.1%. Factors causing repeat radiographic images were patient position 24.1%, exposure factor 15.52%, patient movement 18.97%, artifacts 36.21%, and tool error 5.17%. The percentage of repeat radiographic images decreased in March and April 2025, exceeding the limit set by the Decree of the Minister of Health Number 129/Menkes/S/II/2008, which is ≤ 2%. The dominant factor causing repeat radiographic images is the artifact factor.